Lean concept implementation in a small medium enterprise (SME) pharmaceutical start-up company - Wan Mohd Khairi bin Wan Ibrahim (Kulliyyah of Engineering, International Islamic Universiti Malaysia, 2017)
The domestic pharmaceutical industry has been identified by the Malaysian government as an industry to be developed under its new 11th economic development plan. Most of the homegrown companies within the industry fall under the category of small and medium enterprises (SME) and therefore need to be highly efficient in their operations in order to compete with the multinationals. One approach to achieve an efficient operation is to implement lean manufacturing. However, a relatively small percentage of the local SME companies implement lean manufacturing. The study aims at determining the real success factors in lean implementation through systematic review of relevant literature on implementation of lean manufacturing in local companies, onsite observation of a selected SME company, Global Factor Sdn. Bhd. (GFSB), that claim to have successfully implemented lean manufacturing. The actual implementation of lean manufacturing at Ikop Sdn. Bhd., a SME pharmaceutical start-up company then conducted. Lean tools such as Gemba, value stream mapping (VSM) and spaghetti diagram were used to analyze and improve a selected process at Ikop Sdn. Bhd. The literature review has shown that the implementation of lean manufacturing at Malaysian SMEs involved in pharmaceutical industry is really at its infancy. Study at GFSB indicates that successful implementation of lean manufacturing stem from management support, employee's commitment, government support and knowledge on lean among employees. Gemba activity was conducted at Ikop Sdn. Bhd. by walking through the plant and thus, current VSM and spaghetti diagram were prepared to visualize the waste. Future VSM was created after visualizing the process with elimination of non-value adding activities for the solution. Application of lean tools in Ikop Sdn. Bhd. in improving the manufacturing process cycle efficiency of hand sanitizer, i-Hand 4.0 has shown that the GMP guidelines are not jeopardized. The first Kaizen improvement process has resulted in the reduction of lead time by 46.3%. It may be concluded that implementing lean manufacturing in any Malaysian small and medium startup pharmaceutical company is very beneficial in terms of reducing operational costs and increasing the efficiency and effectiveness and does not conflict with the existing GMP guidelines.